ETIKA KOMUNIKASI DALAM MEDIA SOSIAL BAGI IBU- IBU PKK DI DESA MEKARMUKTI KAB.BANDUNG BARAT (Studi Deskriptif Kualitatif tentang Etika Komunikasi dalam Media Sosial bagi Ibu-Ibu PKK di desa Mekarmukti Kab.Bandung Barat) - Ditha Prasanti; Sri Seti Indriani (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2017)
Abstract. Humans as social beings, certainly put through the process of communication in everyday life. The communication process can be done by using the existing role of the media. The development of technology, the development of the media has become increasingly sophisticated. One of them is the existence of social media. Currently, the communication process becomes easier, so we also know mediated communication, which in this study is through social media. In using social media, of course, can not arbitrarily, but there is a communication ethics that need to be considered. Ethics of communication in social media is what will be studied by researchers. In this digital era, social media development had already entered into the lives of women in rural areas, one of which is the PKK in the village Mekarmukti, Kab. West Bandung. As for the focus of this study are: (1) determine the ethics of communication in social media for the PKK in the village Mekarmukti, Kab.Bandung West; (2) determine the type of social media used by the PKK in the village Mekarmukti, Kab.Bandung West. This study used a qualitative approach with descriptive methods. Researchers used data collection techniques include: observation, interview and documentation study. The results of this study indicate that: (1) the ethics of communication in social media for the PKK include communication ethics in the context of time, the contents of the message, and the communicant; (2) the type of social media used is facebook, BBM, and WhatApp.